Gestión administrativa de la constructora Nomursa S.A - Sanchez Castro, Yoselin Lizzet (2020)
Proper administrative management is essential within any organization because each of the activities carried out have an important influence on organizational performance, which comes hand in hand with the profitability of the company. This case study explains how the different departments of this institution work. The administrative management within a company contributes to supervising that the activities are fully carried out, as the main objective of the investigation of the administrative management of the Constructora Nomursa S.A. is to identify which are the problems that are occurring within this organization. An inefficiency can be observed in the performance of the administration of said company so that all the activities proposed can be carried out, which refers to an inadequate decision-making that does not allow the objectives to be directed. The methodology used for the development of this case study is the type of descriptive and explanatory research, as well as the techniques and instrument of data collection, which allows obtaining more solid results to be able to correctly identify each of the problems of the organization and give a possible solution to it.